1994
DOI: 10.1023/a:1018908326074
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The rate of hydrolysis of methylprednisolone sodium succinate in the freeze dried solid state at 40 degrees C was determined in the presence of two common bulking agents--mannitol and lactose--at two different ratios of drug to excipient. Residual moisture levels were less than 1% in all samples tested, with no significant difference in residual moisture among different formulations. Rate of hydrolysis was significantly higher in mannitol-containing formulations versus lactose-containing formulations, and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…5 fluenced by water mobility rather than the amount of total water. [2][3][4] Although other parameters that could affect the formulation stability should also be considered including the molecular mobility of the drug itself, this report is focusing on the association of water with the formulations and water mobility in the two formulations, both of which could have considerable influence on drug stability, as well as how variations in water contents result in changes to stability superiority.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…5 fluenced by water mobility rather than the amount of total water. [2][3][4] Although other parameters that could affect the formulation stability should also be considered including the molecular mobility of the drug itself, this report is focusing on the association of water with the formulations and water mobility in the two formulations, both of which could have considerable influence on drug stability, as well as how variations in water contents result in changes to stability superiority.…”
Section: Resultsmentioning
confidence: 99%
“…For example, conversion between crystalline and amorphous forms can greatly affect the stability and solubility of drugs in lyophilized formulations. [1][2][3] Residual moisture may have a significant influence on the stability and quality of formulations because water can act not only as a chemical reactant but also as a plasticizer to facilitate the crystallization of amorphous materials.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These results are similar to those obtained by Haikala et al 4) The DSC scans of AAS reference and the freeze-dried sample showed the same pattern. The first endotherm (137- 17) considered that these changes can have an effect on distribution of water within the freeze-dried matrix. However, further work is needed in order to have a better understanding of the pharmaceutical significance of these changes within freeze-dried solids.…”
Section: Evaluation Of the Crystalline Characteristics When Mixtures mentioning
confidence: 99%
“…In general, freeze-dried formulations contain multiple components such as the active pharmaceutical ingredient, bulking agents, lyoprotectants, cryoprotectants, and buffers. The characteristics of freezing and freeze-drying, as well as the physical properties of the freeze-dried solid, have been studied extensively (1)(2)(3)(4). Such investigations yield data that are useful in determining the most desirable formulations and freeze-drying conditions.…”
Section: Introductionmentioning
confidence: 99%